Insight into microenvironment of tumor on the microscopic level with a focus on cancer-associated fibroblasts - Druzhkova, Irina N; Lukina, Maria M; Dudenkova, Varvara; Shimolina, Lubov E; Zagaynova, Elena V; Shirmanova, Marina V (SPIE, 2018)
Cancer-associated fibroblasts (CAFs) are one of the key determinants in the malignant progression of cancer. The subject of this research was metabolic reorganization of CAFs and their participation in collagen cross-linking process. The metabolic differences between normal fibroblasts and CAFs were elucidated using two-photon fluorescence lifetime imaging microscopy (FLIM). Collagen structure in 3D model was assessed using second harmonic generation (SHG) microscopy. We show increased metabolic activity of fibroblasts derived from patient’s colon tumor with a shift to more oxidative metabolism compare to dermal fibroblasts. The results of the study of collagen suggest that CAFs may contribute to the tumor progression through the facilitation of collagen alignment. In general, our findings support the idea of the strong association between cancer cells and fibroblasts and extensive involvement of CAFs in modulation of tumor microenvironment.